Outcomes and process evaluation of a programme integrating physical activity into the primary school mathematics curriculum: The EASY Minds pilot randomised controlled trial. Issue 6 (November 2015) - Riley, Nicholas; Lubans, David R; Morgan, Philip J; Young, Myles
Abstract: Objectives: This study evaluated the feasibility of the 'Encouraging Activity to Stimulate Young (EASY) Minds' programme, a school-based intervention for integrating physical activity (PA) into mathematics lessons. Design: Randomised controlled trial. Methods: Two classes from a single school ( n = 54) were randomised to receive either the 6-week EASY Minds intervention ( n = 27) or follow their usual school programme ( n = 27). The intervention involved the embedding of PA across the pre-existing mathematics programme for 3 × 60 min sessions per week. Changes in PA were measured using accelerometers and 'on task' behaviour was measured using momentary time sampling observation. Results: Using intention-to-treat analysis, significant intervention effects were found for MVPA (9.7%, 95%CI = 7.6, 11.8, p ≤ 0.001) and sedentary time (−22.4%, CI = −24.9, −12.2, p ≤ 0.001) for the intervention group during Mathematics lessons (9.30am–10.30am). Significant intervention effects were also shown for MVPA 8.7% (95% CI = 5.8, 11.6, p ≤ 0.001 and sedentary time −18.6% (95% CI = −24.9, −12.2, p ≤ 0.001) across the whole school day. Furthermore, children displayed significantly greater 'on-task' behaviour across the intervention period with a 19.9% (95%CI = 2.4, 37.4, p ≤ 0.03) mean difference between groups. Conclusions: The EASY Minds programme demonstrated that integrating movement across the primary mathematics syllabus is feasible and efficacious in enhancing school based-PA and improving on-task behaviour in mathematics lessons.